Definition of categories of environmental aspects of civil aviation enterprises (in the example of the international airport "Boryspil") - Маджд, С. М.; Кальницька, Д. Д. (Science-based technologies, 2018)
The article deals with the issues of negative influence on all components of the environmental processes of the state enterprise "Boryspil International Airport". It has been determined that in order to increase environmental safety, it is necessary to introduce a management system that takes into account the various mechanisms and ways of environmental pollution in two stages - environmental analysis and environmental aspects. The authors for the first time developed the main categories of environmental aspects, namely, the resources that are formed when attracting environmental resources into the production system and production, which are formed in the process of production activity. In the course of the research, examples of the consequences of management were given and analyzed their scale of influence. It is proved that the definition of environmental aspects at aviation enterprises is the basis for improving the state of environmental management of the natural environment.